Abuse is not a zero-sum game! The case for zero tolerance of match official physical and verbal abuse. Issue 3 (4th March 2022) - Dawson, Peter; Webb, Tom; Downward, Paul
ABSTRACT: Emergent research has investigated the impact of abuse on the decision of match officials to leave their sport. The existing literature is largely descriptive and qualitative. Based on large surveys of football referees in France and the Netherlands, this paper investigates the factors that are associated with the verbal and physical abuse of the referees and also the association of this abuse with the intentions of referees to quit officiating. The associations are investigated by estimating the marginal effects from bivariate probit and probit models respectively. Bivariate probit estimation reveals a strong correlation between each form of abuse. Both, unsurprisingly, are also positively associated with years of experience of referees. Probit estimation reveals that both forms of abuse, as well as intimidation from refereeing certain teams, are associated with an increased consideration of referees to quit. As increased intention to quit is also associated with the experience of the referee it is likely that the effect of abuse on referee considerations of quitting increase through time. The main conclusions are that the alternative forms of abuse are not zero-sum and both should be targeted by governing bodies to reduce the decline in the number of football referees. The data show that support of referees, for example through mentoring, can offset stated intentions to quit. Highlights This study looks at the factors that are associated with verbal and physical abuse of football referees and the association of this abuse with the intentions to quit. The alternative forms of abuse are not zero-sum and both should be targeted to reduce the decline in referees. Support of referees, for example through mentoring, can offset stated intentions to quit.